Marginalen in de geschiedenis : over beulen, joden, hoeren, zigeuners en andere zondebokken - Vanhemelryck, Fernand (Leuven : Davidsfonds, 2004)
BMLIK
Nederlands
Monografie
Keywords: samenlevingsproblemen